Autoimmune Cytopenias in Chronic Lymphocytic Leukemia. (16th April 2013) - D'Arena, Giovanni; Guariglia, Roberto; La Rocca, Francesco; Trino, Stefania; Condelli, Valentina; De Martino, Laura; De Feo, Vincenzo; Musto, Pellegrino
Abstract : The clinical course of chronic lymphocytic leukemia (CLL) may be complicated at any time by autoimmune phenomena.The most common ones are hematologic disorders, such as autoimmune hemolytic anemia (AIHA) and immune thrombocytopenia (ITP). Pure red cell aplasia (PRCA) and autoimmune agranulocytosis (AG) are, indeed, more rarely seen. However, they are probably underestimated due to the possible misleading presence of cytopenias secondary to leukemic bone marrow involvement or to chemotherapy cytotoxicity. The source of autoantibodies is still uncertain, despite the most convincing data are in favor of the involvement of resting normal B-cells. In general, excluding the specific treatment of underlying CLL, the managementof these complications is not different from that of idiopathic autoimmune cytopenias or of those associated to other causes. Among different therapeutic approaches, monoclonal antibody rituximab, given alone or in combination, has shown to be very effective.